PEMBAGIAN TUGAS POLRI DAN BADAN NARKOTIKA NASIONAL DALAM PENANGANAN KASUS NARKOTIKA - Gusti Muhammad Raja Putra Perdana (Yayasan Pendidikan Tanggui Baimbaian, 2024)
This research discusses the division of tasks between the Indonesian National Police (Polri) and the National Narcotics Agency (BNN) in handling narcotics cases, as well as the obstacles faced by the two institutions, especially in South Kalimantan Province. Based on the analysis of Law No. 35/2009 on Narcotics, there is an imbalance of authority between Polri and BNN investigators in investigating narcotics cases, especially in certain articles. This creates confusion in the community about which agency is authorized to handle drug cases and reduces public trust in drug eradication efforts. The lack of coordination between agencies is one of the main obstacles resulting in the potential for overlapping case handling and reducing the effectiveness of drug eradication. To overcome this problem, it is recommended that authority in handling narcotics crimes be shared equally between the Police and BNN, and strengthened with more synergistic and sustainable regulations. In addition, it is suggested that BNN focus on rehabilitation and research related to narcotics content, thereby reducing the constraints of overlapping authority with the Police. BNN's focus on rehabilitation is expected to have a significant impact on efforts to prevent and cure narcotics in the community.